Fiesta secreta de pizza - Rubin, Adam, 1983-; Salmieri, Daniel, 1983-; Mlawer, Teresa (New York, New York : Puffin Books, an imprint of Penguin Group (USA), 2015)
While Raccoon is eating pizza at his secret pizza party, he sees a masquerade party going on in the house next door to him and joins the fun.
Mientras el Mapache come pizza en su fiesta de pizza secreta, vee que su vecino tiene una fiesta de desfraces y se une la diversión.
Originally published in English as Secret pizza party.
In Spanish.
Keywords: Raccoon -- Juvenile fiction; Parties -- Juvenile fiction; Fiestas -- Novela juvenil; Pizza -- Juvenile fiction; Pizza -- Novela juvenil; Secrecy -- Juvenile fiction; Encubrimiento -- Novela juvenil; Humorous stories -- Juvenile literature; Cuentos humorosos -- Literatura juvenil; Mapaches -- Novela juvenil